2007
DOI: 10.1007/s10495-006-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization determines the delicate balance between the anti- and pro-apoptotic activity of Livin

Abstract: Livin is a member of the Inhibitor of Apoptosis Protein family which inhibits apoptosis induced by a variety of stimuli. We previously identified Livin and demonstrated that following apoptotic stimuli, Livin is cleaved by effector caspases to produce a truncated form with paradoxical pro-apoptotic activity. In the present study, we reveal that while full-length Livin shows diffuse cytoplasmic localization, truncated Livin (tLivin) is found in a peri-nuclear distribution with marked localization to the Golgi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Cisplatin treatment did not change the subcellular localization of Livin A previous report indicated that Livin had both anti-and pro-apoptotic function, which was determined by its different subcellular localization [24]. So we wanted to test the subcellular localization of Livin following cisplatin treatment.…”
Section: Cisplatin Induced Cell Death Was Related To Cell Apoptosismentioning
confidence: 96%
“…Cisplatin treatment did not change the subcellular localization of Livin A previous report indicated that Livin had both anti-and pro-apoptotic function, which was determined by its different subcellular localization [24]. So we wanted to test the subcellular localization of Livin following cisplatin treatment.…”
Section: Cisplatin Induced Cell Death Was Related To Cell Apoptosismentioning
confidence: 96%
“…34 Also, the anti-or pro-apoptotic function of ML-IAP may be regulated by its subcellular localization, as the pro-apoptotic function of truncated ML-IAP has been linked to its perinuclear localization. 35 Survivin represents the smallest member of the IAP protein family and harbors one BIR domain. 8,9 The ability of survivin to inhibit apoptosis has been attributed to its interaction with Smac, to its binding to XIAP, thereby stabilizing the XIAP protein, and to its inhibitory action on mitochondrial apoptosis.…”
Section: Iaps: Structure and Functionmentioning
confidence: 99%
“…34 The limited proteolysis of ML-IAP by caspase-mediated cleavage exposes an N-terminal domain that is critical for localization of truncated ML-IAP to the perinuclear region and its co-localization with the Golgi apparatus. 35 Although this perinuclear localization of truncated ML-IAP has been described to be essential for its pro-apoptotic function, it was found to be per se not sufficient. 35 Moreover, the RING domain of ML-IAP has been implicated to mediate its proapoptotic function.…”
mentioning
confidence: 96%
“…However, p30-Livin a could be stably expressed and showed significant proapoptotic activity in 721.221 EBV-transformed B-cell line but not p28-Livin h (41). Conversely, it was reported that the greater proapoptotic potency of p28-Livin h was more evident than that of p30-Livin a after transfection in the melanoma cell LB33-MEL.A-1 (42). Therefore, the data derived from the experimental model may define Livin isoforms as proapoptotic agents and lead to novel approaches for cancer treatment; however, the diverse activities between the two isoforms displayed in a wide range of cell apoptosis are still uncertain.…”
Section: Versatile Roles Of Livin In the Apoptotic Cascadementioning
confidence: 99%
“…In their article, full-length Livin is detected exclusively in the cytoplasm, whereas the truncated form (tLivin) is located in a perinucleus with marked localization to the Golgi apparatus; the accumulation of tLivin in the nucleus showed positive correlation with the increase in apoptosis. An extensive mutation study theorized that an intact RING domain was identified as the critical residue for the proapoptotic function of tLivin (42). This may provide a possible mechanism by which the RING motif can increase the activity of caspases indirectly in the cell so that the apoptotic barrier can be lowered to allow the cell to undergo apoptosis.…”
Section: Versatile Roles Of Livin In the Apoptotic Cascadementioning
confidence: 99%